Pemberdayaan Masyarakat di Situ Cisanti Desa Cibeureum Kecamatan Kertasari Kabupaten Bandung - Emron Edison; Rieke Sri Rizki Asti Karini (Tourism Scientific Journal, 2022)
Community empowerment is an effort to create and increase the capacity of individual and group communities related to improving their quality of life, independence, and welfare. One of them is through the development and development of tourism. The tourism potential is great, but it has not been managed professionally, so that the community has not felt the acceptance. This is due to the lack of support for community participation. Community empowerment is expected to increase the capacity of the community, both individuals and groups to improve the living standards of the surrounding community. The purpose of the study was to find out how the process of community empowerment was carried out through 3 aspects, namely strengthening capacity, strengthening access and business opportunities and strengthening tourism awareness in Situ Cisanti. The research method used is descriptive qualitative. Data collection techniques by conducting field observations, interviews and documentation with purposive sampling. The conclusion is community activities in implementing the concept of community empowerment approach through tourism development, namely strengthening the capacity and role of the community, strengthening community access and business opportunities, and strengthening tourism awareness. The existence of community empowerment activities has been going well, however, it still cannot be implemented because there is no good cooperation with the community. The benefits of the extension program have not yet been felt in strengthening Tourism Awareness because people do not understand the importance of tourist attractions that grow the economy and community welfare.